Find the first three terms in the binomial expansion of (8-9x)^(2/3) in ascending powers of x

Rewrite (8-9x)^(2/3) as (8(1-(9/8)x)^(2/3)=4(1-(9/8)x)^(2/3). Now apply the C4 binomial formula in the formula booklet, so: 4(1 - ((9/8)x)^(2/3)= 4[ 1 + (2/3)*((-9/8)x) + (2/3)((-9/8)x)^2 .....]= 4[ 1 - (3/4)x + (27/32)x^2 ....]=4 - 3x + (27/8)x^2.... so the first 3 terms are 4 - 3x + (27/8)x^2

Answered by Anthony R. Maths tutor

11135 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the gradient, length and midpoint of the line between (0,0) and (8,8).


find the gradient of y=x3 X0=5


How to find the derivative of arctan(x)


Determine the stationary points of y=(5x^2)/(lnx)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences